Functional and clinical implications of genetic structure in 1686 Italian exomes. Issue 3 (2nd February 2021) - Birolo, Giovanni; Aneli, Serena; Di Gaetano, Cornelia; Cugliari, Giovanni; Russo, Alessia; Allione, Alessandra; Casalone, Elisabetta; Giorgio, Elisa; Paraboschi, Elvezia M.; Ardissino, Diego; Duga, Stefano; Asselta, Rosanna; et al.
Abstract: To reconstruct the phenotypical and clinical implications of the Italian genetic structure, we thoroughly analyzed a whole‐exome sequencing data set comprised of 1686 healthy Italian individuals. We found six previously unreported variants with remarkable frequency differences between Northern and Southern Italy in the HERC2, OR52R1, ADH1B, and THBS4 genes. We reported 36 clinically relevant variants (submitted as pathogenic, risk factors, or drug response in ClinVar) with significant frequency differences between Italy and Europe. We then explored putatively pathogenic variants in the Italian exome. On average, our Italian individuals carried 16.6 protein‐truncating variants (PTVs), with 2.5% of the population having a PTV in one of the 59 American College of Medical Genetics (ACMG) actionable genes. Lastly, we looked for PTVs that are likely to cause Mendelian diseases. We found four heterozygous PTVs in haploinsufficient genes ( KAT6A, PTCH1, and STXBP1 ) and three homozygous PTVs in genes causing recessive diseases ( DPYD, FLG, and PYGM ). Comparing frequencies from our data set to other public databases, like gnomAD, we showed the importance of population‐specific databases for a more accurate assessment of variant pathogenicity. For this reason, we made aggregated frequencies from our data set publicly available as a tool for both clinicians and researchers (http://nigdb.cineca.it ; NIG‐ExIT).